2008
DOI: 10.1111/j.1600-0838.2007.00698.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mouthguard on temporomandibular joint

Abstract: The aim of this study is to examine whether wearing a mouthguard (MG) has an influence on temporomandibular joint (TMJ) components (i.e., the condyle and the articular disk) and whether clenching with a resilient MG has an effect on the same components. Twenty-six healthy volunteers (15 females, 11 males) with an age range of 26-42 years old (median 28 years) participated in this study. Among all 52 joints in the 26 subjects, anterior disk displacement (AntDD) was recognized in 15. Thus, we classified the 52 j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 12 publications
3
20
1
2
Order By: Relevance
“…These changes agreed with another study that found similar changes in joint space during the use of mouthguards (16). Thus, compared with the original model, the condyle was moved downward and forward 0.4 mm and 0.2 mm, respectively, to create models with occlusal splint use.…”
Section: Finite Element Model Generationsupporting
confidence: 74%
“…These changes agreed with another study that found similar changes in joint space during the use of mouthguards (16). Thus, compared with the original model, the condyle was moved downward and forward 0.4 mm and 0.2 mm, respectively, to create models with occlusal splint use.…”
Section: Finite Element Model Generationsupporting
confidence: 74%
“…These changes were in agreement with another study that found similar changes in joint space during the use of mouthguards (16). Thus, compared with the original model, the condyle was moved downward and forward 0.4mm and 0.2mm, respectively, for create models with occlusal splint use.…”
Section: Methodssupporting
confidence: 91%
“…Whereas, in analyses involving large deformations, the use of non-linear elastic behavior would be required. 16 An evolution in disc characterization was the development of a model that represented the interaction between fluid and solid constituents as a biphasic or poro-elastic model that accounted for the shock-absorbing properties of the disc. 7 This type of model was also used to represent hyaline cartilages, however, it was not the best option for modeling the mechanical response of the TMJ disc, because the concentration of glycosaminoglycans (GAGs) in this fibrocartilaginous soft tissues was lower, which could result in reduced drag between the fluid and solid matrix.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations